Adobe Photoshop : a complete course and compendium of features - Laskevitch, Stephen (Rocky Nook Inc., 2023)
Adobe Photoshop: A Complete Course and Compendium of Features is your guide to creating, editing, and enhancing images and designs in Adobe Photoshop. Whether you’re retouching a photograph, generating designs for social media, or combining images into composite creations, Photoshop is the tool for you—and this book will teach you what you need to know. This second edition has been fully revised and updated to cover the newest features of Photoshop.